The Devil and the Dolce Vita : Catholic Attempts to Save Italy's Soul, 1948-1974 - Domenico, Roy Palmer (Book collections on Project MUSE., 2021)
"Examines the cultural politics of Italian Catholics in the thirty years following World War II, and explores the sentiments of those who tried to renew a traditional Catholic ethos in an age of consumerism and secularism"--